The cost of protecting resources: a cross-sectional study on the interaction between LMX and role ambiguity on work addiction and burnout among Canadian first-level healthcare managers - Maisonneuve, Francis; Groulx, Patrick; Galy, Anaïs; Chênevert, Denis; Cossette, Michel (Frontiers in Psychology, 2024)
Introduction Using the conservation of resources (COR) theory, our study explores the interaction between role ambiguity and leader-member exchange (LMX) quality on burnout using work addiction as a mediator among Canadian first-level healthcare managers. Methods Cross-sectional data was collected among 165 first-level managers working in healthcare with the support of interprofessional associations in Canada. Linear regression was used to test the presented hypotheses. Results Work addiction fully mediated the positive relationship between role ambiguity and burnout among first-level managers. In addition, high LMX exacerbated both the direct and indirect effects of role ambiguity. Conclusion Our study contributes by identifying role ambiguity as a context under which LMX can have adverse effects for first-level managers in healthcare. Moreover, work addiction acted as a mediator, theorized as a risky resource investment which depletes managers’ resources. Having a good relationship with their team further entices managers to develop a pathological relationship with their work to protect its members, which in turn is related to higher levels of burnout.